Mild synthesis of poly(HEMA)-networks as well-defined nanoparticles in supercritical carbon dioxide - Parilti, R.; Alaimo, D.; Grignard, B.; Boury, F.; Howdle, S.M.; Jerome, C. (Royal Society of Chemistry, 2017)
Free-radical dispersion polymerisation of 2-hydroxyethyl methacrylate was carried out in supercritical carbon dioxide (scCO2) in the presence of stabilisers based on polyethylene oxide (PEO) and poly(heptadecafluorodecyl acrylate) (PFDA). Different architectures of copolymers (random, palm-tree and diblock) were tested for their surface tension, cloud point and as a stabilising agent. The diblock architecture was found to be the best candidate resulting in poly(HEMA) spherical particles with a size of 316 nm. Furthermore, the effect of the CO2-phobic block (PEO) in the diblock architecture was investigated by using three different chain lengths (1000, 2000, 5000 g mol−1). By optimizing the stabiliser composition and structure, mild reaction conditions have been identified allowing us to obtain well-defined spherical cross-linked poly(HEMA) particles with a mean diameter of unprecedented low size (216 nm) at a temperature as low as 35 °C.